Japanese Encephalitis Virus Persistence in Porcine Tonsils Is Associated With a Weak Induction of the Innate Immune Response, an Absence of IFNγ mRNA Expression, and a Decreased Frequency of CD4+CD8+ Double-Positive T Cells - Redant, Valerie; Favoreel, Herman W.; Dallmeier, Kai; Van Campe, Willem; De Regge, Nick (Frontiers in Cellular and Infection Microbiology, 2022)
In humans, Japanese encephalitis virus (JEV) causes a devastating neurotropic disease with high mortality, whereas in pigs, the virus only causes mild symptoms. Besides tropism to the central nervous system, JEV seems to harbor a particular tropism for the tonsils in pigs. This secondary lymphoid organ appears to act as a reservoir for the virus, and we show that it is found up to 21 days post infection at high viral titers. The immune response in the tonsils was studied over time upon intradermal inoculation of pigs. Entry of the virus in the tonsils was accompanied by a significant increase in anti-viral OAS1 and IFNβ mRNA expression. This limited antiviral response was, however, not sufficient to stop JEV replication, and importantly, no IFNγ or innate inflammatory cytokine mRNA expression could be observed. Strikingly, the persistence of JEV in tonsils was also associated with a significant decreased frequency of CD4+CD8+ double-positive T lymphocytes. Furthermore, it is important to note that JEV persistence in tonsils occurred despite a strong induction of the adaptive immune response. JEV-specific antibodies were found after 6 days post infection in serum, and cell-mediated immune responses upon NS3 restimulation of PBMCs from experimentally infected pigs showed that CD4+CD8+ double-positive T cells were found to display the most prominent proliferation and IFNγ production among lymphocyte subtypes. Taken together, these results suggest that an inadequate induction of the innate immune response and the absence of an IFNγ antiviral response contribute to the persistence of JEV in the tonsils and is associated with a decrease in the frequency of CD4+CD8+ double-positive T cells.